A distinct isoform of ZNF207 controls self-renewal and pluripotency of human embryonic stem cells - Fang Fang (Nature Portfolio, 2018)
Self-renewal and pluripotency of human embryonic stem cells (hESCs) depends upon the function of the transcription factor OCT4. Here, the authors identified proteins associated with the OCT4 enhancer, notably ZNF207 that maintains both pluripotency and differentiation towards ectoderm through isoform switching.